Kufs’ disease: diagnostic difficulties in the examination of extracerebral biopsies - Lewandowska, Eliza; Lipczyńska-Łojkowska, Wanda; Modzelewska, Joanna; Wierzba-Bobrowicz, Teresa; Mierzewska, Hanna; Szpak, Grażyna M.; Pasennik, Elżbieta; Jachińska, Katarzyna (Folia Neuropathologica, 2009)
Kufs’ disease or NCL4 (neuronal ceroid lipofuscinosis type 4) is a rare and poorly characterized, adult-onset form of NCL. The mutation in gene CLN, underlying Kufs’ disease, still remains unknown. The diagnosis of this disease is difficult because it is based only on clinical and ultrastructural examinations. We report the case of a 45-year-old woman referred to the Neurological Department with suspicion of Creutzfeldt-Jakob disease (CJD). CJD as well as infectious, autoimmune and some lysosomal diseases were excluded. Since clinical symptoms, i.e. psychotic, auditory and visual hallucinations as well as behavioural disturbances, still suggested metabolic or neurodegenerative disease, a skin and muscle biopsy was performed. On ultrastructural examination the muscle biopsy revealed the subsarcolemmal accumulation of lipofuscin, lipofuscin-like and granular osmiophilic deposits (GRODs). The most unique fingerprint deposits (FP) and curvilinear profiles (CP) for diagnosis of Kufs’ disease were located in vascular smooth muscle cells (VSMCs). In these cells lipofuscin-like deposits and GRODs were also visible. The fact that FP and CP were found exclusively in VSMCs jointly with clinical and laboratory data allows us to diagnose Kufs’ disease in our patient.